Planning of Plastic Surgery Practice to Say Sayonara - Saleem, Lakshmi (Indian Journal of Plastic Surgery, 2020)
Having seen the retired life of our professors both in general and plastic surgery and how lonely and isolated they were toward the end of their lives prompted me to discuss the retirement plans. The retirement from active surgical practice is indeed difficult and more so in plastic surgery. I feel that it needs meticulous planning for setting up a successful practice and when to say sayonara, just like treatment planning of any surgical procedure for perfect execution! At the end of M.Ch training, one should analyze oneself about the goal of the professional life and commit oneself to either a solo/group practice as an independent institutional practice or in a corporate set-up or choose a state/central government set-up with some academic position. A successful plastic surgical practice is every plastic surgeon’s dream and it comprises professional and financial successes with a sense of personal achievement. The factors involved in the selection of practice are family obligations—if parents or spouse are in medical profession with an existing establishment—individual talent, willingness to learn newer techniques, and acceptance of help from the other professional colleagues. At the same time, life needs to be balanced between the professional and family commitments without ignoring either of them with a deep social and community responsibility. But what is the correct time to say sayonara? The timing of retirement is difficult to get right, but the basic additional principle that guides one is “Primum non-nocere”—do no harm—to the receiver.
Keywords: plastic surgery; retirement; timing